Macroeconomics And Bank-Specific Factors Affecting Liquidity: A Study Of Nepali Commercial Banks - Ojha, Pushpa Raj (Journal of Business and Social Sciences, 2018)
This paper aims to examine the form and pattern of liquidity, NPL, return on assets, CAR, return on equity, GDP, inflation and interbank rate in Nepalese commercial banks. The study is intended to analyze the relationship between liquidity and bank specific variables in Nepalese commercial banks. The key findings stated that there is significant relation between numbers of variables that impacts on the liquidity performance of Nepalese commercial banks. The panel data of commercial banks from 2010/11 to 2016/17 has been taken for the purpose of the research. Mean, standard deviation, correlation and multiple regression analysis have been used to diagnose date to meet the specific objectives of research. The results reveal that there is significant influence of ROA, ROE, NPL, GDP and IBR on LIQ.